2008
DOI: 10.1111/j.1478-4408.2008.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atmospheric plasma treatment on the dyeability of cotton fabrics by acid dyes

Abstract: Cotton fabrics were treated with air and argon atmospheric plasma for surface activation. Activated surfaces were grafted with two different amine compounds: ethylenediamine and triethylenetetramine. Pretreated cotton was dyed with acid dye and the effects of pretreatment on the colour strength, as well as the washing, rubbing and the light fastness of the dyeings, were investigated. Colour yield results showed that grafted ethylenediamine and triethylenetetramine enhance the dyeability of cotton fabric with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 8 publications
(10 reference statements)
0
42
1
Order By: Relevance
“…Karahan et al [8,102] observed that LTP treatment caused micro-cracks and tiny groves on cotton fabric surface because of the etching effect. Also, it was found that the argon plasma treatment was more effective than the air plasma treatment.…”
Section: Natural Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…Karahan et al [8,102] observed that LTP treatment caused micro-cracks and tiny groves on cotton fabric surface because of the etching effect. Also, it was found that the argon plasma treatment was more effective than the air plasma treatment.…”
Section: Natural Materialsmentioning
confidence: 98%
“…Karahan et al [102] reported that air and argon atmospheric-pressure plasma treatments considerably improved the pilling resistance of cotton fabrics. This result was attributed to the reduction in the hairiness of the fabric.…”
Section: Influencing Physical Properties Of Fibersmentioning
confidence: 99%
“…In all treatments, argon gas was used under a constant power of 130 W with 0,5 l/min gas flow. Argon gas was selected due to its effects on surface activation of cotton fabrics as observed from the previous studies [11,18,19,20]. The samples were treated for 20 secs in the plasma.…”
Section: Methodsmentioning
confidence: 99%
“…As seen from the images, the untreated cotton surface is quite smooth and clean whereas the combined process treated cotton surface is rougher and full of microcracks, which occurred because of the etching effect of plasma treatment [11,18,19,20]. Also the particles of cyclodextrin and antibacterial agent can be observed on both washed and unwashed samples.…”
Section: Sem Analysismentioning
confidence: 99%
“…Balu et al (2008) have employed oxygen plasma processing technique to give superhydrophobicity to cellulose fabrics. To improve dyeability, air and argon atmospheric plasma has been used for surface activation of cotton fabrics (Karahan et al 2008). Better and faster dye uptake on textiles was achieved using surface modification of wool and cotton fabrics after environmentally safe enzyme pretreatment (Kantouch et al 2006;Vankar and Shanker 2008).…”
Section: Introductionmentioning
confidence: 99%